A.H.M. Jones and the later Roman Empire - Gwynn, David M. (David Morton), 1975- (Brill's series on the early Middle Ages ;, 2008)
The appearance in 1964 of AHM Jones' "The Later Roman Empire 284-602: A Social, Economic, and Administrative Survey" transformed the study of the Late Antique world. This volume reassess the impact of Jones' great work, the influences that shaped his scholarship, and the legacy he left for later generations.